2005
DOI: 10.1016/j.jacc.2005.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ischemic Limbs Based on Local Recruitment of Vascular Endothelial Growth Factor-Producing Inflammatory Cells With Ultrasonic Microbubble Destruction

Abstract: Ultrasonic destruction of microbubbles delivered to the ischemic limbs can recruit inflammatory cells producing VEGF, which is followed by neovascularization and functional improvement, and thus has a therapeutic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 27 publications
2
34
0
3
Order By: Relevance
“…22,23 Postulated mechanisms for this biologic effect have included the recruitment of inflammatory cells, platelets, or bone marrow stem cells, 23 the release of platelet-derived proinflammatory factors which may attract circulating endothelial progenitor cells, 24 or the via the recruitment of VEGF-producing inflammatory cells. 25 Unlike these studies, we found that control microbubble destruction did not result in increases in total or capillary blood flow, and are in keeping with other studies of ultrasound-mediated gene delivery. 12,13 Differences in ultrasound transmit frequency and acoustic power, microbubble composition and doses, methods of blood flow determination, and vessel density measurements between studies could have accounted for these differences.…”
Section: Discussionsupporting
confidence: 90%
“…22,23 Postulated mechanisms for this biologic effect have included the recruitment of inflammatory cells, platelets, or bone marrow stem cells, 23 the release of platelet-derived proinflammatory factors which may attract circulating endothelial progenitor cells, 24 or the via the recruitment of VEGF-producing inflammatory cells. 25 Unlike these studies, we found that control microbubble destruction did not result in increases in total or capillary blood flow, and are in keeping with other studies of ultrasound-mediated gene delivery. 12,13 Differences in ultrasound transmit frequency and acoustic power, microbubble composition and doses, methods of blood flow determination, and vessel density measurements between studies could have accounted for these differences.…”
Section: Discussionsupporting
confidence: 90%
“…Currently it is believed that inhibition of hTLR4 or hTLR4 related downstream activity can subsequently attenuate plaque formation or even plaque rupture [35,36]. Of note, formation of collateralarteriogenesis which is an important mechanism to increase blood flow to ischemic parts [37,38] is mediated by inflammatory cytokines [39,40]. The beneficial effects of hTLR4 in arteriogenesis were seen by Grote study [41].…”
Section: Discussionmentioning
confidence: 96%
“…This test has been used in the functional evaluation of arteriogenesis and angiogenesis in animals following induction of hind limb ischemia, and improved vessel formation was found to correlate with time to exhaustion [15][16][17][18]. Time to exhaustion was defined as a characteristic change in gait.…”
Section: Functional Assay: Treadmillmentioning
confidence: 99%